Giant Breast Myofibroblastoma: A Rare Case of Benign Breast Tumor in a Postmenopausal Woman - Henry I. Lyimo; Zephania D. P. Gega; Alex B. Mashaka; Angela T. Mlole; Saida K. Abeid; Petro J. Mabindi; Nashivai E. Kivuyo; Ally H. Mwanga (Case Reports in Surgery)
Conclusion: This case presentation underscores the importance of considering MFB as a potential differential for breast tumors especially in menopausal women. Tissue biopsy for histopathology and IHC staining form the cornerstone for accurate diagnosis and appropriate management.